Germany : 2011 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Germany. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Germany's economic growth and recovery from the global crisis are explained in this study. Tax, education, and innovation policies are specific measures supported by the authorities. External and financial shocks received by Germany and other outward spillovers are outlined. Germany has a high current account and international assets. From a long-term perspective, rebalancing of public finances to promote growth is desirable. Stress tests are conducted to confirm the capital buffers. Finally, the banking system of Germany reflects significant policy measures and economic recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet